2020
DOI: 10.1155/2020/1754975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,3,7,8-Tetrachlorodibenzo-p-dioxin on T Cell Differentiation in Primary Biliary Cholangitis

Abstract: Exposure to dioxins, such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), is reported to affect the autoimmune system and increase the risk of autoimmune disease. Generally, dioxin exerts its toxicity via aryl hydrocarbon receptor (AhR). Primary biliary cholangitis (PBC) is a chronic autoimmune disease, and its pathogenesis involves the interplay between immune and environmental factors. This study showed the effect of dendritic cells (DCs) activated by TCDD on naïve CD4+ T cell differentiation in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Regarding primary biliary cholangitis (PBC), there is emerging evidence that AHR might be involved in dysregulation of T cell responses. Consistent with the notion that AHR-activating dioxins might be risk factors for the development of autoimmune disease [44], She et al reported that DCs derived from PBC patients but not from healthy donors enhanced inflammatory Th1 and Th17 differentiation upon TCDD exposure [44]. In dnTGFβRIIdeficient mice, a spontaneous model for PBC, microarray analysis linked dysfunctional Treg showing reduced suppressive capacity and acquisition of inflammatory features to the down-regulation of AHR and other critical transcription factors in Tregs.…”
Section: Ahr In Liver Immune Homeostasismentioning
confidence: 87%
“…Regarding primary biliary cholangitis (PBC), there is emerging evidence that AHR might be involved in dysregulation of T cell responses. Consistent with the notion that AHR-activating dioxins might be risk factors for the development of autoimmune disease [44], She et al reported that DCs derived from PBC patients but not from healthy donors enhanced inflammatory Th1 and Th17 differentiation upon TCDD exposure [44]. In dnTGFβRIIdeficient mice, a spontaneous model for PBC, microarray analysis linked dysfunctional Treg showing reduced suppressive capacity and acquisition of inflammatory features to the down-regulation of AHR and other critical transcription factors in Tregs.…”
Section: Ahr In Liver Immune Homeostasismentioning
confidence: 87%
“…Notably, AhR activation has been demonstrated playing a role in the pathogenesis of other liver diseases, like hepatitis C, where the AhR-cytochrome P4501A1 pathway was found to favor lipid accumulation along with virus replication and assembly ( 84 ); and primary biliary cholangitis (PBC) where dioxin activated dendritic cells promoted differentiation of naïve CD4-cells, derived from PBC patients, into effector Th1 and Th17-cells ( 85 ). Importance of xenobiotics as triggers for PBC was also reported in earlier investigations ( 86 , 87 ).…”
Section: Treg Impairment In Aih: the Role Of Cd39mentioning
confidence: 99%
“…Upon binding to its ligands, AhR translocates to the cell nucleus where it forms a complex with the aryl-hydrocarbon-receptor-nuclear-translocator (ARNT), the AhR canonical partner, to regulate various genes, including cytochrome P450 enzymes, cytokines (IL-22, IL-17, IL-10), drug transporters (ABCB1, ABCC4) and CD39. Notably, AhR activation has been demonstrated playing a role in the pathogenesis of other liver diseases, like hepatitis C, where the AhR-cytochrome P4501A1 pathway was found to favor lipid accumulation along with virus replication and assembly (84); and primary biliary cholangitis (PBC) where dioxin activated dendritic cells promoted differentiation of naïve CD4-cells, derived from PBC patients, into effector Th1 and Th17-cells (85). Importance of xenobiotics as triggers for PBC was also reported in earlier investigations (86,87).…”
Section: Treg Impairment In Aih: the Role Of Cd39mentioning
confidence: 99%
“…This section focuses on the role of AHR activation by EDCs in the activity of DCs. Our search identified 11 articles, including TCDD as AHR ligand (Kinoshita et al 2006;Lee et al 2007;Vogel et al 2008Vogel et al , 2014Vogel et al , 2013Chmill et al 2010;Jin et al 2010;Simones and Shepherd 2011;Rohlman et al 2013;Kado et al 2017;Beamer et al 2020), 2 for BPs (Bankoti et al 2010;Svajger et al 2016;She and Liu 2020) and none for PFAS or FRs.…”
Section: Ahr Mechanistic Pathway In Dendritic Cellsmentioning
confidence: 99%
“…On the other hand, we identified 2 articles reporting that high concentrations of BPs can also affect DCs maturation through AHR activation ( Svajger et al 2016;She and Liu 2020). For instance, it has been shown in humans that BPA exposure results in the induction of moDCs maturation and activation (She and Liu 2020).…”
Section: Ahr Mechanistic Pathway In Dendritic Cellsmentioning
confidence: 99%